Temporal migration patterns and mating tactics influence size-assortative mating in Rana temporaria - Dittrich, Carolin (Behav Ecol, 2018)
Assortative mating is a common pattern in sexually reproducing species, but the mechanisms leading to assortment remain poorly understood. By using the European common frog (Rana temporaria) as a model, we aim to understand the mechanisms leading to size-assortative mating in amphibians. With data from natural populations collected over several years, we first show a consistent pattern of size-assortative mating across our 2 study populations. We subsequently ask if assortative mating may be explained by mate availability due to temporal segregation of migrating individuals with specific sizes. With additional experiments, we finally assess whether size-assortative mating is adaptive, i.e. influenced by mating competition among males, or by reduced fertilization in size-mismatched pairs. We find that size-assortative mating is in accordance with differences in mate availability during migration, where larger individuals of both sexes reach breeding ponds earlier than smaller individuals. We observe an indiscriminate mate choice behavior of small males and an advantage of larger males pairing with females during scramble competition. The tactic of small males, to be faster and less discriminative than large males, may increase their chances to get access to females. Experimental tests indicate that the fertilization success is not affected by size assortment. However, since female fecundity is highly correlated with body size, males preferring larger females should maximize their number of offspring. Therefore, we conclude that in this frog species mate choice is more complex than formerly believed.